Response of edible amaranth cultivar to salt stress led to Cd mobilization in rhizosphere soil: A metabolomic analysis. (October 2018) - Guo, Shi-Hong; Hu, Ni; Li, Qu-Sheng; Yang, Ping; Wang, Li-Li; Xu, Zhi-Min; Chen, Hui-Jun; He, Bao-Yan; Zeng, Eddy Y.
Abstract: The present study aimed to investigate the metabolic response of edible amaranth cultivars to salt stress and the induced rhizosphere effects on Cd mobilization in soil. Two edible amaranth cultivars ( Amaranthus mangostanus L.), Quanhong (low-Cd accumulator; LC) and Liuye (high-Cd accumulator; HC), were subject to salinity treatment in both soil and hydroponic cultures. The total amount of mobilized Cd in rhizosphere soil under salinity treatment increased by 2.78-fold in LC cultivar and 4.36-fold in HC cultivar compared with controls, with 51.2% in LC cultivar and 80.5% in HC cultivar being attributed to biological mobilization of salinity. Multivariate statistical analysis generated from metabolite profiles in both rhizosphere soil and root revealed clear discrimination between control and salt treated samples. Tricarboxylic acid cycle in root was up-regulated to cope with salinity treatment, which promoted release of organic acids from root. The increased accumulation of organic acids in rhizosphere under salt stress obviously promoted soil Cd mobility. These results suggested that salinity promoted release of organic acids from root and enhanced soil Cd mobilization and accumulation in edible amaranth cultivar in soil culture. Graphical abstract: Highlights: Metabolic profiling of root changed significantly under salt stress. Salinity stress significantly enhanced TCA cycle metabolism in root. Enhanced TCA cycle metabolism increased organic acid secretion of root. Increased organic acids in rhizosphere promoted soil Cd mobility. More metabolites were up-regulated by salinity in the root of HC cultivar. Abstract : We found that salinity significantly promoted release of organic acids from root and enhanced soil Cd mobilization and accumulation in edible amaranth cultivar in soil culture.